First the form of the equation would be;

y= mx + b, where m is the slop.

==> y = (-3/4)x + b

when x = 0, then y = (-3/4) 0 + b= b

then the point where the line intersect with the y-axis is (0,b)

when y = 0 ,...

## Unlock

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

First the form of the equation would be;

y= mx + b, where m is the slop.

==> y = (-3/4)x + b

when x = 0, then y = (-3/4) 0 + b= b

then the point where the line intersect with the y-axis is (0,b)

when y = 0 , then (-3/4) x +b= 0

==> (3/4) x= b

==> x= (4/3)b

then the point where the line intersect with the x-axis is (4b/3, 0)

but, the area of the triangle is:

A= 1/2 * 4b/3 * b

24 = 1/2 * 4b/3 *b

24 = 1/2 * 4b^2/3 = 4b^2 /6

==> b^2 = 24*6/4

==> b^2 = 36

==> b = 6, -6

then the eqution of teh slope is:

y = (-3/4) x + 6 and y= (-3/4)x -6